Sociological Study of Socio-Cultural Conditions among the Gujjars in South Kashmir: Examining the Socio-cultural Access and Challenges among Gujjars in South Kashmir (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Schedule tribes do not only live in hinter lands, dense forests, bereft of basic amenities of modern life, but are economically poor, socially backward, but culturally sound. The socio-cultural changes occurring among schedule tribes of Kashmir is more than the general population of region. Their housing, sanitation, electricity, health care facilities are very low sub-standard than other sections of population. The literacy rate among schedule tribes of Kashmir is also very low. Still schedule tribes have less efforts and interest towards gaining education. JK Gujjars who are mainly Muslims carry with itself the age old traditions and customs of prehistoric time. This paper is based on Primary as well as secondary sources of data and tries to analysis the magnitude of socio-cultural access of different parameters. At the end of this paper there are some recommendations which need to be addressed at the ground level to develop the socio-economic and cultural aspects of Gujjars of the south Kashmir.